Highly Stable White Light-Emitting Diodes Based on Quantum-Dots Dispersed Into the Backlight Lens for Display Backlight - Xin Yang; Xu-Yan Lan; Yu-Sheng Liu; Hui-Yu Yang; Yi Li; Shu-Wen Zheng; Yong Zhang (IEEE Photonics Journal)
A novel package structure has been developed to fabricate quantum-dot (QD) white light-emitting diodes (WLEDs) by dispersing QDs into the backlight lens and integrating them with blue light-emitting diode to form white light. For this in-lens encapsulation structure, the luminous efficiency and lifetime of QD-WLEDs can reach 90 lm/W and 1000 h, which is 25 times longer than that of QD-WLEDs with on-chip encapsulation structure. Furthermore, a 32-inch prototype liquid crystal display TV shows a wide color gamut of 108% under the National Television Systems Committee standard with this in-lens encapsulation structure. The improvement performance should be attributed to providing a hermetic encapsulation environment preventing oxygen and water from reacting with the QDs and reducing the temperature of QDs due to in-lens package structure. Our results demonstrate that the in-lens solution can be a promising application in display backlight.